Determination of Rukyatul Hilal in the Harmonization of Science and Religion - Kharisatul Amanah (Yayasan Insan Cendekia Nusantara, 2024)
As Muslims who observe fasting almost every year, of course this cannot be seprated from the determination of the start of Ramadan and Shawwal. In this case, there are also differences in determination, especially since in Indonesia itself there are several different schools. Determining the start of Ramadhan and Shawwal need to be made base on rukyat al-hilal. Currently, an path to a witness is the main basis for accepting testimony of seeing the new moon. However, in practice there is almost never any clarification regarding the conditions for fulfilling the crescent moon testimony, because it turns out that in practice in tne field, there are still many who cannot identify with certainty whether they are seeing a crescent moon or another object. Science and technology have developed so rapidly. Scientific evidence is verry necessary to guarantee the certainty of the shahadah which is used as a guideline for the itsbat at the beginning of the months of ramadan and shawwal. Then in this study, it was concluded that science and technology, especially in the fields of optics and digital imaging, were proven to be able to help increase objectivity in rukyat al-hilal testimony.